Modeling extreme ultraviolet attosecond pulses in modulated waveguides - Toşa Valer; Tóth Istvan Ferenc; Gherman Ana Maria Mihaela; Ciriolo Anna Gabriella; Martínez Vázquez Rebeca; Nistico Alessio; Stagira Salvatore (EPJ Web of Conferences, 2024)
We explore via numerical modeling the generation of very short photon wavelengths in hollow core waveguides (HCW) filled with He gas at high pressures. Propagation of femtosecond driving pulses is first solved using a split-step method and tested against other methods. The propagation along the HCW reveals mode beating seen in quasi-periodic oscillations of the field intensity and phase which in turn will determine the single atom response to the field. We explore both cylindrical and conical HCW in which the guide diameter varies along the propagation direction. This second configuration generates very high harmonic orders in a regime of quasi-phase matching. We found three spectral ranges which show amplification, at 3.5, 7.6, and 11-13 nm, which are of great interest given their practical applications in spectroscopy, XUV metrology and photolithography.